High- and low-frequency transcutaneous electrical nerve stimulation does not reduce experimental pain in elderly individuals. Issue 10 (October 2015) - Bergeron-Vézina, Kayla; Corriveau, Hélène; Martel, Marylie; Harvey, Marie-Philippe; Léonard, Guillaume
Abstract : Abstract: Despite its widespread clinical use, the efficacy of transcutaneous electrical nerve stimulation (TENS) remains poorly documented in elderly individuals. In this randomized, double-blind crossover study, we compared the efficacy of high-frequency (HF), low-frequency (LF), and placebo (P) TENS in a group of 15 elderly adults (mean age: 67 ± 5 years). The effect of HF-, LF-, and P-TENS was also evaluated in a group of 15 young individuals (26 ± 5 years; same study design) to validate the effectiveness of the TENS protocols that were used in the elderly group. Each participant came to the laboratory on 3 separate occasions to receive, in random order, HF-, LF-, and P-TENS. Pain intensity and pain perception thresholds were assessed before, during, and after TENS, using an experimental heat pain paradigm. For the young group, there was a significant decrease in pain intensity during and after HF- and LF-TENS when compared with baseline, with both HF- and LF-TENS being superior to P-TENS. In the older group, HF- and LF-TENS did not reduce pain when compared with baseline and no difference was observed between the 2 active TENS sessions and P-TENS. High-frequency, LF-, and P-TENS all increased pain thresholds in young individuals, whereas in older individuals, only LF-TENS increased pain thresholds. Taken together, these results suggest that TENS is effective in young, but not in older, individuals. Future studies should be conducted to confirm these results in pain populations and to identify strategies that could enhance the effect of TENS in the elderly. Abstract : High- and low-frequency transcutaneous electrical nerve stimulation is effective for reducing experimental heat pain in young individuals but not in older individuals.